Cross-region comparison intellectual capital and its impact on Islamic banks performance - Prasojo Prasojo; Winwin Yadiati; Tettet Fitrijanti; Memed Sueb (Economies, 2022)
This paper uses the value-added intellectual coefficient (VAIC) to assess the performance of Islamic banks (IBs) by measuring return on assets (ROA) and income from financing Islamic banks (IFIB). The model tests the relationship between intellectual capital (IC) and IB performance in various regions using a panel data regression methodology with a fixed-effects model and IB financial data for the period 2009-2019 from the BankScope database. The empirical results show that VAIC has a significant positive effect on IB performance using both ROA and IFIB proxies. Furthermore, human capital and capital employed efficiency have a positive relationship with ROA and IFIB, while structural capital efficiency has a relationship with ROA, but is not related to IFIB. The results can be used by companies in strategic decision making related to IC, especially human capital, structural capital, and employed capital.
Keywords: 330; IFIB; intellectual capital; Islamic bank; ROA; VAIC